AXIOLOGICAL APPROACH TO THE ANALYSIS OF SPIRITUAL CULTURE OF UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2025)
The value of spiritual culture is a key factor in the formation and development of national ideology. This scientific article argues that spiritual culture is a value, that spirituality and culture are interconnected and inseparable. In addition, the role and influence of spiritual culture in the development of national ideology is scientifically and philosophically investigated. The content is illuminated through the concept of axiology, which is a value philosophy. Scientific research was carried out using concepts such as axiology, value assessment, value approach, moral quality of a spiritual person. The scientific conclusion was made that our country has a rich spiritual heritage, which is a key tool for the comprehensive development of young people through spiritual heritage, especially in shaping their national ideological worldview.